Storm Clouds on the Horizon: On the Emerging Need to Tighten Selection Policies - Johnston, Kathryn; Farah, Lou; Baker, Joe (Frontiers in Sports and Active Living, 2021)
Athlete selection is fundamental in elite sport, occurring regularly throughout an athlete's development. Research in this area reveals the accuracy of these decisions is questionable in even the most elite sport environments and athletes are increasingly disputing these decisions as unfair and punitive. As a countermeasure to these dispute and arbitration practices, many elite sport systems have created policies where coaches must outline and stand behind the criteria used for their selection decisions. Selection criteria policies have the potential to help encourage fair selection practices by holding selectors accountable to their selection criteria, but their implementation also has the potential to wrongfully nudge selectors toward developing more defendable, but less-accurate selection practices. The paper concludes with 10 suggestions to help support practitioners when implementing selection criteria.